Bicentric evaluation of employee satisfaction, patient safety and treatment quality: comparing different Health Information System (HIS) solutions - Brand, Matthias; Boehm, Felix; Kaisers, Udo X.; Fehling, Patrick; Hoffmann, Thomas K.; Rotter, Nicole; Ludwig, Sonja; Theodoraki, Marie-Nicole (BMC health services research, 2025)
Transforming healthcare related work processes through digitization may help to address the growing demands placed on employees by enhancing user satisfaction and may have an impact on patient safety and treatment quality. Hereby, different approaches reaching from multimodal, workflow-specific systems to more uniform and comprehensive formats have been introduced.
Online veröffentlicht: 17. November 2025
Gesehen am 03.02.2026